ANALISIS KUALITAS SOAL BUATAN GURU BIOLOGI DALAM KEMAMPUAN BERPIKIR TINGKAT TINGGI SISWA - Musdalifah Musdalifah; St. Syamsudduha; Nursalam Nursalam (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2020)
This research was a quantitative descriptive study that aimed to find out the quality of questions made by teachers of SMA Negeri 10 Gowa in terms of the level of difficulty, discrimination item, and to determine the ability of these questions to measure the high-level thinking students in SMA Negeri 10 Gowa. The sample in this study was 36 students. Data collection technique was documentation, by collecting all daily questions, answer keys, and the marks of student answers of Biology class XI of SMA Negeri 10 Gowa. The instrument used in this study was a review of the Higher Order Thinking (HOTS) adapted from a module of Making HOTS Questions published by the Education and Culture Office. The data of this study were analyzed quantitatively and qualitatively. Based on the results of the quantitative analysis, the level of difficulty of the question description used in daily tests was quite good, while questions for multiple-choice categorized as good. The quality of discrimination items for both essays and multiple-choice questions categorized as poor. The results of a qualitative analysis found that there were no questions categorized as HOTS, but all of these questions had very good in use and construction of language.